Creating a Mograph Title Sequence: 2 Animating in After Effects. - Stern, Eran; Harauz, Nick (linkedin.com, 2020)
Turn your initial concept into a full-fledged title sequence. Learn how to work with Adobe Premiere Pro and After Effects to bring your ideas to life.